MOTIVASI ORANG TUA MEMILIH TAMAN KANAK-KANAK SEBAGAI WADAH SOSIALISASI PENDIDIKAN ANAK USIA DINI DI TK KARTIKA JAYA KECAMATAN TERNATE UTARA KOTA TERNATE - Hamus, Nur Alaina A. (HOLISTIK, Journal Of Social and Culture, 2017)
Education is the key to all the social changes that have been internationally recognized without educational reform, it is impossible to carry out political reform, economic reform and social reform. Reforms related to human attitudes and human ahitudes can only be chaged through educational proses. Early chilldhood education (PAUD) is one important factors in education in indonesia which expocted to improve human resources. Early childhood education (PAUD) is and effort aimed at the child from birtt. One from of early childhood education (PAUD) that existed on the formal education path that is kindergarten (TK). The chid in the kindergarten (TK) is and indindual figure who is in the process development, which is the process of behavioralchange from the immnature to the mature from simple to complex, a process of human evolution of dependence into an independent adult creature. The research use qualitative methods, as well as technques of data collection management, that is by observation, interview, and documentation. This study dscusses the motivation of parents, so choose make kindergarden as a place of socialization for thar children that is Kartika Jaya kindergarten. Based on the research results of the existence of Kartika Jaya kindergarten has a positiv impact for the familly. Familes themseives have their own reasons for sending their children to this Kartika Jaya kindergarten, both in terms of busyness, incompetence and lack of confidence to finance. The authors classty the familly into three, that is upperclass familles, middle class familes and lower class familes.Â Keyword: motivation, socialization, PAUD